Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Efektifitas Kerja Guru di MTs Miftahul Ulum Gunung Geni Kecamatan Banyuanyar Kabupaten Probolinggo - Agung Yatiningrum (Fakultas Ekonomi Universitas Panca Marga, 2015)
This research determine the effect of Leadership and Effectiveness Against Work Discipline Teachers Working in MTs Miftahul Ulum Gunung Geni Banyuanyar Probolinggo. The population in this research was the total number of teachers MTs Miftahul Ulum Gunung Geni as many as 20 people. While the data collection methods used were observation, interviews, questionnaires, documentation and literature studies. This type of research with manifold quantitative correlation approach in order to determine the relationship and influence of leadership and discipline to the effectiveness of teachers' work, and in the process the author uses helping of software such as programs Statistical Product and Service Solutions (SPSS, v.15) with the data used in this study were independent variables are Leadership (X1) and Work Discipline (X2), and the dependent variable is Work Effectiveness (Y). From the data processing obtained an equation Y = 9.493 + 0.378 + X2 0,381X1 which means the value of the constant a = 9.493 states that if the respondents' assessment of the leadership and discipline unchanged (fixed), the amount of work amounted to 9.494 Effectiveness of regression b1 = 0.381 states that every additional assessment Leadership at one point, then it affects the increase in effectiveness of the work amounted to 0.432 if the discipline of work has not changed (fixed), and the regression coefficient b2 = 0.378 states that whenever there is additional appraisal work discipline by one point, then it affects the increase in effectiveness of work amounted to 0.378 if the leadership does not change (fixed). The results showed a partial t test = 2,004 X1 and X2 = 2,488 bigger than t table is 1.734 with a significant 0.05. This means that all independent variables (Leadership and discipline of work) has a significant influence on the effectiveness of the work of teachers in MTs Miftahul Ulum Mount Geni Banyuanyar Probolinggo. The coefficient of determination (R) is 0.434 x 100% = 43.40%, this suggests that the effect of variable X (Leadership and discipline) to variations (up and down) Y (Effectiveness of work) amounted to 43.40%, while the balance of 56.60% comes from other factors in addition to leadership and discipline. The test results indicate that the hypothesis that the writer to convey unacceptable that